If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + 1)(3x + -9) = 0 Reorder the terms: 4(1 + 2x)(3x + -9) = 0 Reorder the terms: 4(1 + 2x)(-9 + 3x) = 0 Multiply (1 + 2x) * (-9 + 3x) 4(1(-9 + 3x) + 2x * (-9 + 3x)) = 0 4((-9 * 1 + 3x * 1) + 2x * (-9 + 3x)) = 0 4((-9 + 3x) + 2x * (-9 + 3x)) = 0 4(-9 + 3x + (-9 * 2x + 3x * 2x)) = 0 4(-9 + 3x + (-18x + 6x2)) = 0 Combine like terms: 3x + -18x = -15x 4(-9 + -15x + 6x2) = 0 (-9 * 4 + -15x * 4 + 6x2 * 4) = 0 (-36 + -60x + 24x2) = 0 Solving -36 + -60x + 24x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '12'. 12(-3 + -5x + 2x2) = 0 Factor a trinomial. 12((-1 + -2x)(3 + -1x)) = 0 Ignore the factor 12.Subproblem 1
Set the factor '(-1 + -2x)' equal to zero and attempt to solve: Simplifying -1 + -2x = 0 Solving -1 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -2x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -2x = 0 + 1 -2x = 0 + 1 Combine like terms: 0 + 1 = 1 -2x = 1 Divide each side by '-2'. x = -0.5 Simplifying x = -0.5Subproblem 2
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3Solution
x = {-0.5, 3}
| 100+10x=0+15x | | 6y+24x=48 | | 99999999+1= | | f(a)=6a-5 | | (2/3)^3x=8/27 | | 4x^4+3x+3=0 | | 9y+3x=-18 | | 2a-b+c=18 | | 2x+0.5x=0 | | 4x^2+9y^2-4x+12y+5=0 | | r=4g+rz | | 3(f-4)=-6 | | x+39+40+20=180 | | -3x-5x=-2x | | 10(s-9)=169 | | 16a^2*12a^5= | | 20+40+39+x=180 | | 2a-2=3a-1 | | x-4/6=3/7 | | 8x+14y=180 | | B+4b=8b-b | | 35x+37(1-x)=100 | | 39+x+20+40=180 | | 35x+37(1-x)=1 | | 39+40+20=180 | | 14=y+c | | 4/5(2x)=360 | | (x-7)(3x+1)= | | 6+4(3+6)+5= | | 10+g*20=14+g*0 | | 7x+9=10x+(-3+3x) | | 2x+3y+5z=120 |